The Impact Of Teacher Professional Competence On The Effectiveness Of Classroom Management In Secondary Schools - Arji Yunandar (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Teacher professional competence is a key factor influencing the quality of learning in the classroom. This study aims to examine the impact of teacher professional competence on the effectiveness of classroom management in secondary schools. A quantitative approach with a correlational research design was employed. The study utilized a survey method, with data collected through questionnaires distributed to respondents. The population of this study comprised all junior high school teachers in Lembah Seulawah District, Aceh Besar, totaling 102 teachers. A proportional random sampling technique was used to select 81 teachers, calculated using the Slovin formula. Data were collected through questionnaires and analyzed using the product-moment correlation test. The results revealed that teacher professional competence significantly influences classroom management. The Pearson correlation test yielded a coefficient of 0.730 (p = 0.000), indicating a strong positive relationship. This means that higher teacher professional competence corresponds to more effective classroom management. The very low significance value (p = 0.000) confirms that this relationship is statistically significant and not due to chance.